The relationship between sprint ability, agility and vertical jump performance in young soccer players - Köklü, Y.; Alemdaroglu, U.; Özkan, A.; Koz, M.; Ersöz, G. (Science & Sports, 2015)
Objective: The purpose of this study was to examine the relationships between speed, agility and vertical jump performance in young soccer players. Material and methods: Fifteen soccer players (average age 16.0 ± 0.8 years; average height 168.4 ± 4.7 cm; average body mass 62.6 ± 7.7 kg; average training age 6.0 ± 2.0 years) participated in this study voluntarily. The sprinting ability of each player was determined using 10-m and 30-m single-sprint times; zigzag agility with the ball (ZAWB) and without the ball (ZAWHB) test times were used to determine their agility; and squat jump (SJ) and countermovement jump (CMJ) heights were used for the determination of vertical jump ability. Results: The results of Pearson Product Moment Correlation analysis indicated moderate to strong correlations between 10-meter sprint times and 30-meter sprint times (r = 0.714; P = 0.01) and ZAWHB (r = 0.567; P = 0.02). Similarly, 30-meter sprint times were moderate to strong correlated with CMJ ability (r = -0.599; P = 0.02) and ZAWHB (r = 0.744; P = 0.01). A strong correlation was also found between CMJ ability and SJ ability (r = 0.706; P = 0.01) and between CMJ ability and ZAWHB (r = -0.769; P = 0.01). In addition, SJ ability was strongly correlated with ZAWHB (r = -0.712; P = 0.01). Finally, ZAWHB was moderate correlated with ZAWB (r = 0.566; P = 0.02). In conclusion, the findings of the present study indicated that there is a significant correlation between sprint ability and agility. In addition, significant correlations were found both between vertical jumping ability and sprinting ability and between vertical jumping ability and ZAWHB test performance in soccer players. Conclusion: The results of the study therefore suggest that speed, agility without the ball and vertical jumping ability share common physiological and biomechanical determinants.